Criminal Responsibility for Perpetrators of Murder of Schizophrenia: A Comparative Study of Decision Number 2353/Pid.B/2018/PN.Mdn WITH 150/Pid.B/2024/PN.Jkt.Brt - Muhammad Zidane Hasymi; Handar Subhandi Bakhtiar (UNIVERSITAS PAKUAN, 2026)
This writing study examines criminal responsibility for murder perpetrators suffering from schizophrenia through a comparative analysis of Decision Number 2353/Pid.B/2018/PN.Mdn and Decision Number 150/Pid.B/2024/PN.Jkt.Brt. This study is motivated by inconsistencies in judicial decisions involving offenders with similar mental disorders, which create legal uncertainty and raise concerns about justice and legal protection. This study aims to analyze how judges assess criminal responsibility by considering juridical and psychological aspects, especially in interpreting Article 44 of the Old Criminal Code and evaluating psychiatric evidence such as Visum et Repertum Psychiatric (VeRP). This research uses normative juridical methods using legal, comparative, and conceptual approaches, focusing on legal materials such as laws, doctrines, and court decisions. The findings revealed that differences in judicial decisions were influenced by the interpretation of expert testimony, the quality and strength of psychiatric evidence, and the judge's perspective on the defendant's mental capacity (toerekeningsvatbaarheid). The Medan decision concluded that the defendant was not criminally responsible and mandated medical treatment, while the Jakarta decision found the defendant guilty of the fulfillment of the element of intent. The study offers a novelty by emphasizing the need for clearer legal guidelines and consistent standards in assessing criminal responsibility for individuals with schizophrenia, as well as integrating rehabilitative, restorative, and corrective approaches in Indonesia's reformed criminal justice system.